Addition, alteration, reconstruction. Three models of adaptive re-use - Marco Russo (Agathón)
The article investigates the subject of re-use of the existing heritage through the analysis of three Chinese projects, carried out over the last five years. They show that it is possible to work with existing structures without necessarily resorting to its total alteration. This ‘new’ generation of Chinese architects, who studied in the USA and Europe, disavows the concept of making a clean slate in order to develop solutions based on the rediscovery of local techniques and materials. Among the key projects of this new trend the paper will dwell on the recovery of a factory by Vector Architects, the addition into existing structures by Horizontal Design and the ideal reconstruction of the imperial kilns by Studio Zhu-Pei.